The Use of Bulk Fill Resin-Based Composite in the Sealing of Cavity with Margins in Radicular Cementum - Francesco, Puleio; Gabriele, Cervino; Fiorillo, Luca; Giuseppe, Miragliotta; Antonella, Squillacioti; Giancarlo, Bruno; Mirta, Pinizzotto; Mendes Tribst, João Paulo; Lo Giudice, Roberto (European Journal of Dentistry, 2021)
The aim of this systematic review was to evaluate if the newly introduced bulk fill resin-based composite provides a better marginal sealing in cavity preparations with margins in dental cementum. The population investigation comparison outcome (PICO) framework was: in cavity preparation with margins in dental cementum of human extracted teeth, do bulk fill resin base composites provide a better marginal sealing than non-bulk fill resin-based composites? We performed our research on April 21, 2020. Two authors independently evaluated the abstract and titles for eligibility criteria. Two authors independently extracted the data and assessed the risk of bias in single studies. After the initial screening of 400 abstract and titles, the full text of the articles, that could meet the eligibility criteria, were obtained via the university library. A total of 36 full-text articles were evaluated; 11 articles were finally eligible for the review. Eight studies showed statistically differences, but not significant, in the marginal sealing between bulk fill and nonbulk fill resin-based composite (p > 0.05). One study showed statistically significant differences: SonicFill and Grandio showed better marginal sealing than GrandioSo and SDR(r) (Sirona Dentsply, New York, United States) and the latter two showed better marginal sealing than Filtek Supreme (p < 0.05). One study showed statistically significant less marginal gap of SDR than Filtek Bulk Fill (p = 0.0015) and Filtek Supreme (p < 0.0001). One study showed SDR to have a significantly higher microleakage than the other materials tested (p < 0.05). Based on our current literature review, there are not enough data to establish if bulk fill resin base composite provides a better or a worse marginal sealing at cementum margins.
Keywords: bulk fill resin; composite; conservative dentistry; radicular cementum; sealing